The Use of the WhatsApp Application in the Learning Process in Class IX C of SMP Negeri 2 Tondano - Pangalila, Theodorus; L. S, Herni; Ferry Lourens Sampel, (Technium Social Sciences Journal, 2023)
The purpose of this study is to determine whether or not employing the WhatsApp application as a learning assistance medium is successful. This study was carried out because social media apps now have a significant impact on the learning process, one of which is at SMP Negeri 2 Tondano. The issues presented in this study include the process of using WhatsApp in the learning process of students at SMP Negeri 2 Tondano, as well as the hurdles in adopting the usage of WhatsApp in the learning process. A qualitative methodology with descriptive research was employed in this study. Interviews, observations, and recording of instructors and students in class 9C were used to obtain research data. According to the findings of the research, the WhatsApp application has features that can support it as a medium in the learning process. WhatsApp is also capable of making the teacher's job easier if they are unable to enter the classroom due to external assignments or meetings that cannot be left behind. Students who are unable to attend can also send assignments and notifications to the teacher concerned via WhatsApp. The hurdles include that not all students have cell phones, that learning is less effective because the teacher does not always explain the content directly, and that the teacher cannot perceive the students' seriousness in studying. WhatsApp, as an intriguing tool, is a helpful medium in the learning process, however it must be balanced by the teacher's function of entering the classroom to explain the subject and the processes for carrying out assignments directly.